External apical root resorption after molar space closure with miniscrew as anchorage: a tomographic evaluation (Research, Society and Development, 2020)
Objective: The purpose of this retrospective study was to evaluate and quantify external apical root resorption (EARR) in molars after masialization into atrophic alveolar ridge area. Materials and Methods: The sample consisted of 11 patients, five women and six men, and a total of 16 molars, both superior and inferior (seven in the maxilla and nine in the mandible). The age range was 19 to 55 years at the beginning of treatment (initial mean age of 36 years and 5 months), with an average treatment time of 23 months. Tooth movement was performed with mini-implant anchorage using NiTi springs, using a mean force of 300 grams. The sample was evaluated using cone-beam CT scans (CBCT) in two periods, at the beginning of the treatment (T1) and after 4 mm of movement (T2). Root resorption was measured by the difference in root lengths (T2-T1). Using the distance from the floor of the pulp chamber to the root apex as a reference. Root length was measured using specific software (OnDemand3Ddental) and was analyzed using the paired t-test, adopting a significance level of 5%. Results: There was statistically significant resorption only in the mesial and distal roots, with a mean reduction  of  0.69 mm  in  the mesial  root (-6.2%) and  0.83 mm  in  the  distal  root (-7.4%). Conclusion: Space closure after dental movement in an atrophic alveolar ridge was identified as a risk factor for ARR. However, the amount of ARR could be considered clinically irrelevant.